The role of thyroid hormones in carotid arterial wall remodeling in women - Saric Maida Seferovic; Jurasic Miljenka-Jelena; Budincevic Hrvoje; Milosevic Milan; Kranjcec Bojana; Kovacic Sanja; Leskovar Jana; Demarin Vida (Sciendo, 2022)
Introduction: Thyroid hormones affect the cardiovascular system, but the precise mechanisms of their effects on the development of atherosclerosis are not entirely clear. The relationship between subclinical hypothyroidism, dyslipidemia and carotid atherosclerosis has been widely investigated, but the findings were controversial. The aim of the present study was to determine whether female subjects with subclinical hypothyroidism (SHypo) have increased carotid intima-media thickness (IMT) compared with euthyroid subjects, as well as to examine the association of SHypo, carotid atherosclerosis and dyslipidemia.